Improving Efficiency of Round Robin Scheduling Using Ascending Quantum And Minumim-Maxumum Burst Time - Ali Jbaeer Dawood (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Round Robin (RR) is a kind of process algorithms, where the time quantum is fixed along the processes execution. In the other hand it depending on the First Come First Serve (FCFS) algorithm. Also RR performs in timesharing system by given each process static Time Quantum (TQ). In this paper, The TQ studied to improve the efficiency of RR and performs the degrades with respect to Context Switching (CS), Average Wait Time (AWT) and Average Turned Around Time (ATAT) that an overhead on the system. Thus, the new approach was proposed to calculate the TQ, known as Ascending Quantum and Minumim-Maxumum Round Robin (AQMMRR). The processes were ascending with shortest remaining burst time and calculate the TQ from multiply the summation of minimum and maximum BT by (80) percentage. The experimental result shows that AQMMRR performs better than RR and comparing with other two related works.